2020
DOI: 10.1177/1043659620938127
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Genetic Literacy in a Small Hispanic Population

Abstract: Introduction: Genetic literacy recognizes one’s ability to gather, understand, and apply genomic information to make informed health care choices and social decisions. A limited understanding of genomic literacy carries the potential for poor health outcomes. The aim of this pilot study was to determine the usefulness of an assessment tool to ascertain genetic literacy in a small Hispanic clinic population. Methodology: Mixed-method, cross-sectional pilot study requiring forward-back translation of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…It is well-suited for the German sample but proves to be too demanding for the Greek group, as indicated by a significant floor effect. When examining other samples where the KGEI and KMGG have been employed, it becomes apparent that the KGEI tends to have a moderate level of difficulty, while the KMGG appears relatively challenging ( Carver et al, 2017 ; Gericke et al, 2017 ; Tornabene et al, 2020 ; Subasic et al, 2021 ), which aligns with the findings in our samples. Carver et al (2017) reported that the difficulty of the KMGG was associated with items related to epigenetics, which posed significant challenges for participants but were retained to reflect the current state of research.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It is well-suited for the German sample but proves to be too demanding for the Greek group, as indicated by a significant floor effect. When examining other samples where the KGEI and KMGG have been employed, it becomes apparent that the KGEI tends to have a moderate level of difficulty, while the KMGG appears relatively challenging ( Carver et al, 2017 ; Gericke et al, 2017 ; Tornabene et al, 2020 ; Subasic et al, 2021 ), which aligns with the findings in our samples. Carver et al (2017) reported that the difficulty of the KMGG was associated with items related to epigenetics, which posed significant challenges for participants but were retained to reflect the current state of research.…”
Section: Discussionsupporting
confidence: 85%
“…While Carver et al (2017), Tornabene et al (2020), andGericke et al (2017) reported internal consistency values ranging from 0.61 to 0.69 for the KGEI and KMGG, we observed substantially higher values. Similarly, the Spanish translation by Subasic et al (2021) reported 0.782 for the KGEI and 0.926 for the KMGG, although it is important to acknowledge that Subasic's sample was relatively small, consisting of only 20 participants.…”
Section: Internal Consistency and Retestmentioning
confidence: 98%
“…While the importance of genetic testing has recently emerged within the context of personalized medicine, there have been limited studies on genetic testing strategies for Mexican-origin adults and no studies to date specifically for men ( 13 16 ). However, low levels of knowledge and awareness about genetic testing have previously been reported ( 16 ), and prior findings demonstrate that Hispanics may not understand risk within the context of genetics due to limited genetic literacy defined as the ability to obtain, process, understand, and use genetic information ( 17 , 18 ). This may be due in part to limited health care access and health information faced by many Hispanics in the U.S. ( 19 ).…”
Section: Introductionmentioning
confidence: 99%